2020
DOI: 10.1111/ffe.13226
|View full text |Cite
|
Sign up to set email alerts
|

On the application of laser shock peening for retardation of surface fatigue cracks in laser beam‐welded AA6056

Abstract: The present study aims to investigate the extent to which the fatigue behaviour of laser beam-welded AA6056-T6 butt joints with an already existing crack can be improved through the application of laser shock peening. Ultrasonic testing was utilized for in situ (nondestructive) measurement of fatigue crack growth during the fatigue test. This procedure allowed the preparation of welded specimens with surface fatigue cracks with a depth of approximately 1.2 mm. The precracked specimens showed a 20% reduction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…Therefore, the positive effect of LSP, which was shown is this study, is assumed to remain the same in high cycle fatigue regime. The positive effect of LSP on the retardation of fatigue cracks in the high cycle fatigue regime was also demonstrated in a previous study of Kashaev et al [14].…”
Section: Fatigue Testssupporting
confidence: 79%
See 2 more Smart Citations
“…Therefore, the positive effect of LSP, which was shown is this study, is assumed to remain the same in high cycle fatigue regime. The positive effect of LSP on the retardation of fatigue cracks in the high cycle fatigue regime was also demonstrated in a previous study of Kashaev et al [14].…”
Section: Fatigue Testssupporting
confidence: 79%
“…Lorenzino and Navarro [20] reported that an initial growth of the resonant frequency can be attributed to the effect of cyclic hardening in the material, while a drop in the frequency is associated with a crack growth. Similar observations were also reported in [14]. To monitor the fatigue crack growth, a visual inspection was carried out using an optical microscope on both specimen surfaces.…”
Section: Fatigue Testing Of Specimens and Preparation Of Specimens Wisupporting
confidence: 71%
See 1 more Smart Citation
“…Note that similar observations of how weld defects affect the fatigue behaviour have also been reported for FS aluminium weldments, where the crack either initiates at surface irregularities like weld undercuts and flash ridges or at root defects. 10,[37][38][39][40] In that sense, there is no significant difference between a HYB weld and a FS weld. Figure 8 shows a comparison of the calculated S-N curves for the BM and the two sets of welded specimens, EZ and EZ red .…”
Section: Fracture Analysismentioning
confidence: 94%
“…However, they found that LSP could not inhibit the initiation of cracks at scribe roots. Similarly, Kashaev et al 18 employed LSP to restore the fatigue life of laser beam‐welded AA6056‐T6 butt joints with a pre‐existing crack to the level of specimens tested in as‐welded condition. Sikhamov et al 19 exhibited healing of initial cracks in AA2024‐T3 alloy with a fastener hole due to LSP, which improved fatigue life by increasing the crack growth period.…”
Section: Introductionmentioning
confidence: 99%